Organisation, technological change and skills use over time: A longitudinal study on linked employee surveys. (31st December 2021) - Dhondt, Steven; Kraan, Karolus O.; Bal, Michiel
Abstract: The impact of technological change on the content of jobs and accompanying skills is a central topic across disciplines. To date, ample research has directly linked the technological change to shifts in skills use; however, organisational change is rarely considered as an influencing factor. Based on a panel survey, this paper uses a Luhmannian approach to understand the relationship between technological change and organisational context. This theory is tested quantitatively and shows the importance of considering the working environment's nature when studying skills changes. The results show small effects by the technological change on changing skills use but larger effects by changes in the working environment. Recommendations for future research and practical implications are discussed.